2022
DOI: 10.1177/02654075221113031
|View full text |Cite
|
Sign up to set email alerts
|

Support me in the good times too: Interpersonal emotion regulation, perceived social support, and loneliness among mothers of children with autism spectrum disorder

Abstract: Although loneliness is an experience that mothers of children with autism spectrum disorder (ASD) may face, it has not been widely explored. Having a supportive social environment that is also effective in emotion regulation may provide feelings of security necessary for one to feel less lonely. The present study examined loneliness levels among mothers of children with ASD (vs. without ASD) and explored interpersonal resources (interpersonal emotion regulation and perceived social support) that might contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…As the pandemic ensued, women began facing ever higher amounts of unpaid care work, economic precarity, healthcare resource deficits, restricted movements, and for many, an increasing amount of gender-based violence (United Nations Entity for Gender Equality and the Empowerment of Women, 2020). Social isolation measures that halted in-person gatherings, including religious services and fellowship, exacerbated feelings of loneliness, burden, and purposelessness, especially for mothers of children with special needs (Laslo-Roth et al, 2022; Schnabel et al, 2020). Thus, religiously conservative women bound by their rigid family gender roles felt increasingly anxious about their mothering abilities to protect their children’s health and mistrustful of the government and the medical community as neither were able to contain the virus (Bracewell, 2021).…”
Section: “Do I Have Something For ‘Q’ou”: Wellness Mlms and Pastel Qanonmentioning
confidence: 99%
“…As the pandemic ensued, women began facing ever higher amounts of unpaid care work, economic precarity, healthcare resource deficits, restricted movements, and for many, an increasing amount of gender-based violence (United Nations Entity for Gender Equality and the Empowerment of Women, 2020). Social isolation measures that halted in-person gatherings, including religious services and fellowship, exacerbated feelings of loneliness, burden, and purposelessness, especially for mothers of children with special needs (Laslo-Roth et al, 2022; Schnabel et al, 2020). Thus, religiously conservative women bound by their rigid family gender roles felt increasingly anxious about their mothering abilities to protect their children’s health and mistrustful of the government and the medical community as neither were able to contain the virus (Bracewell, 2021).…”
Section: “Do I Have Something For ‘Q’ou”: Wellness Mlms and Pastel Qanonmentioning
confidence: 99%
“…These factors may lead to increased loneliness and enhanced parental distress and may negatively affect all members of the family (Gosztyła & Prokopiak, 2019). However, only a few studies have directly examined the experience of loneliness among parents of children with ASD (e.g., Gosztyła & Prokopiak, 2019; Laslo‐Roth et al, 2022; Lu et al, 2021; Sipowicz et al, 2022). In a recent study conducted among 39 parents of autistic children (16% fathers) who were visiting a mental health clinic, and 45 parents of nonautistic children, it was found that loneliness mediated the relationship between stress and depressive symptoms, indicating that higher levels of stress were related to higher levels of loneliness, which, in turn, were related to more depressive symptoms (Sipowicz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies that emphasized the important role of loneliness among parents of children with ASD included more representative samples of parents from the community but focused only on mothers or included a very small number of fathers (e.g., Gosztyła & Prokopiak, 2019; Laslo‐Roth et al, 2022; Lu et al, 2021). In addition, and to the best of our knowledge, none of these studies compared the loneliness experience of fathers of children with and without ASD in order to understand whether loneliness is a unique risk factor for fathers of children with ASD that differs from the experience of fathers in general.…”
Section: Introductionmentioning
confidence: 99%